Reinforced embankments theory and practice - Shercliff, D. A. (Thomas Telford, 1990)
Increased demands for improved rail and road links, and the lack of good quality building land are forcing engineers to construct embankments with steeper side slopes and on lower grade soils. The use of reinforcing geotextiles is one way of overcoming the problems this presents.